Respuesta :
Answer:
[tex]\large\boxed{x=\dfrac{4}{3}=1\dfrac{1}{3}}[/tex]
Step-by-step explanation:
[tex]x-\dfrac{2}{3}+\dfrac{1}{6}=\dfrac{5}{6}\qquad\text{multiply both sides by 6}\\\\6x-6\!\!\!\!\diagup^2\cdot\left(\dfrac{2}{3\!\!\!\!\diagup_1}\right)+6\!\!\!\!\diagup^1\cdot\left(\dfrac{1}{6\!\!\!\!\diagup_1}\right)=6\!\!\!\!\diagup^1\cdot\left(\dfrac{5}{6\!\!\!\!\diagup_1}\right)\\\\6x-(2)(2)+1=5\\\\6x-4+1=5\\\\6x-3=5\qquad\text{add 3 to both sides}\\\\6x=8\qquad\text{divide both sides by 6}\\\\x=\dfrac{8}{6}\\\\x=\dfrac{8:2}{6:2}\\\\x=\dfrac{4}{3}[/tex]